Powders Based on Ca2P2O7-CaCO3-H2O System as Model Objects for the Development of Bioceramics - Kristina Peranidze; Tatiana V. Safronova; Yaroslav Filippov; Gilyana Kazakova; Tatiana Shatalova; Julietta V. Rau (Ceramics, 2022)
Nanoscale powders of hydrated Ca2P2O7, CaCO3, and a product of mixed-anionic composition containing P2O74− and CO32− anions were synthesized from aqueous solutions of Ca(CH3COO)2, pyrophosphoric acid (H4P2O7), and/or (NH4)2CO3. Pyrophosphoric acid was previously obtained on the basis of the ion exchange process from Na4P2O7 solution and H+-cationite resin for further introduction into the reactions as an anionic precursor. The phase composition of powders after the syntheses was represented by bioresorbable phases of X-ray amorphous hydrated Ca2P2O7 phase, calcite and vaterite polymorphs of CaCO3. Based on synthesized powders, simple cylindrical constructions were prepared via mechanical pressing and fired in the temperature range of 600–800 °C. Surface morphology observation showed the presence of bimodal porosity with pore sizes up to 200 nm and 2 μm, which is likely to ensure tight particle packing and roughness of the sample surface required for the differentiation of osteogenic cells. Thus, the prepared ceramic samples can be further examined as model objects for bone tissue repair.